Relevance and linguistic meaning : the semantics and pragmatics of discourse markers - Blakemore, Diane (Cambridge studies in linguistics, 2002)
In this new and important study of the analysis of discourse markers, Diane Blakemore argues that the exercise in classification that has dominated discourse marker research should be replaced by the investigation of the way in which linguistic expressions contribute to the inferential processes involved in utterance understanding.